Aluminum magnesium aspirin pharmaceutical composition and preparation method thereof
By using single-layer tablet preparation method and wet granulation coating technology in aluminum-magnesium Pilin tablets, the problems of complex production process and aspirin side effects are solved, and the stability and dissolution of the preparation are achieved. The improvement in degree simplifies production processes and reduces costs.
Patent Information
- Application Number
- CN202310233276.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-13
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-03-13
AI Technical Summary
The production process of existing aluminum-magnesium-pilin tablets is complex and has low efficiency. The content uniformity of the double-layer tablets fluctuates greatly, material waste is serious, and the gastrointestinal side effects of aspirin are relatively high, which limits its long-term use.
The preparation method of single-layer tablets includes the preparation of aluminum-magnesium granules through wet granulation and coating technology, and mixed with aspirin with pressure The tablets were finally dried.
The stability and dissolution of the preparation are improved, and the hydrolysis catalytic effect of aluminum magnesium ions and weak alkalinity on aspirin is reduced, side effects are reduced, production process is simplified, and costs are reduced.
Smart Images

Figure GDA0005227318980000021 
Figure GDA0005227318980000041 
Figure GDA0005227318980000071
Abstract
Description
Technical Field
[0001] The invention belongs to the field of medical technology, and specifically relates to an aluminum-magnesium-pillide pharmaceutical composition and a preparation method thereof. Background Art
[0002] Aluminum-magnesium aspirin tablets (Ⅱ) are used in cases of unstable angina, acute myocardial infarction, local ischemic cerebrovascular disorders, etc. where aspirin is needed to inhibit platelet adhesion and aggregation, but the patient cannot tolerate the gastrointestinal reactions of aspirin.
[0003] Aspirin, the main ingredient of aluminum-magnesium aspirin tablets, has a history of more than 100 years. It is not only an antipyretic and analgesic, but also can significantly reduce blood coagulation, and has anti-thrombotic and thrombolytic effects. For patients with a history of heart disease or stroke, aspirin can reduce the risk of unstable angina by more than 35%, and can reduce the incidence of stroke or death in patients with transient ischemic attacks by 25%. Although aspirin plays an important role in multiple therapeutic areas such as anti-platelet aggregation, it has a greater irritation to the gastric mucosa and a high incidence of gastrointestinal side effects. It is not suitable for long-term use, which restricts its clinical use.
[0004] In 2001, Japan's LION company developed and launched aluminum-magnesium aspirin tablets under the trade name BUFFERIN. Its main advantages are that on the one hand, it can reduce the adverse stimulation of aspirin to the stomach and significantly reduce the incidence of gastric mucosal erosion and ulcers; on the other hand, it can also increase its absorption. Alkaline drugs can accelerate gastric emptying, thereby allowing aspirin to quickly enter the main absorption site - the small intestine.
[0005] At present, the aluminum-magnesium aspirin tablets produced by LION Company on the market are double-layer tablets, which require the use of a special double-layer tablet press during the production process. They also have problems such as low production efficiency, large fluctuations in the content uniformity of the double-layer tablets, and serious material waste. Therefore, there is an urgent need to provide a formula and process that is more suitable for production under normal conditions. Summary of the invention
[0006] The purpose of the present invention is to provide a new aluminum-magnesium-pillide tablet pharmaceutical composition, which has good preparation stability and better dissolution.
[0007] Another object of the present invention is to provide a method for preparing the aluminum-magnesium-pillide tablet pharmaceutical composition, which is suitable for industrial production.
[0008] Specifically, the present invention provides:
[0009] An aluminum-magnesium aspirin tablet composition comprises: aspirin, aluminum glycolate, heavy magnesium carbonate, weakly alkaline or neutral gastric-soluble polymer, plasticizer, microcrystalline cellulose, neutral fast-dissolving material, filler and adhesive.
[0010] The aluminum-magnesium-pillin tablet composition comprises the following components in parts by weight:
[0011]
[0012] The weakly alkaline or neutral gastric soluble polymer is selected from one of methyl methacrylate amine alkyl ester copolymer, PVP K30, and low-viscosity HPMC.
[0013] The plasticizer is selected from one of glycerol, triethyl citrate and sorbitol.
[0014] The neutral instant material is selected from one or more of mannitol, pregelatinized starch slurry, starch slurry and dextrin slurry.
[0015] A method for preparing aluminum-magnesium aspirin tablets comprises the following steps:
[0016] Step 1: After sieving the microcrystalline cellulose and the filler respectively, mix them with the binding solution I, and perform one-step granulation to obtain auxiliary material granules for standby use;
[0017] Step 2: wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II, and weakly alkaline or neutral gastric soluble polymer to obtain aluminum-magnesium particles;
[0018] Step 3: coating the aluminum-magnesium particles obtained in step 2 with a coating liquid to obtain coated aluminum-magnesium particles;
[0019] Step 4: mixing aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and the filler, and tableting to obtain a semi-finished tablet;
[0020] Step 5: Dry the semi-finished tablet obtained in step 4 to obtain the final product.
[0021] The filler is one or more of corn starch, starch, lactose and sorbitol.
[0022] The adhesive solution I comprises mannitol, pregelatinized starch and water, wherein the weight ratio of mannitol, pregelatinized starch and water is: 0.2-0.3: 0.04-0.06: 0.8-1.2.
[0023] The adhesive solution II comprises triethyl citrate, povidone K30 and water, wherein the weight ratio of povidone K30, triethyl citrate and water is 0.15-0.25:0.08-0.12:0.8-1.2.
[0024] The coating liquid comprises mannitol, pregelatinized starch, titanium dioxide and water, wherein the weight ratio of mannitol, pregelatinized starch, titanium dioxide and water is 0.2-0.3: 0.06-0.07: 0.03-0.04: 0.8-1.2.
[0025] Compared with the prior art, the present invention has the following advantages and positive effects:
[0026] 1. The product of the present invention is a single-layer tablet. Compared with a double-layer tablet, it reduces the complexity of the process and equipment and reduces the cost; improves the tablet hardness, is more wear-resistant and stronger, and also avoids the defects of separation of the two layers of the double-layer tablet and easy discoloration near the contact surface;
[0027] 2. The present invention coats the aluminum and magnesium particles, and then mixes and compresses them into tablets after the particles are in an isolated state, thereby isolating the aluminum and magnesium from contacting aspirin, and significantly reducing the catalytic effect of aluminum and magnesium ions and weak alkalinity on the hydrolysis of aspirin;
[0028] 3. The product production operation of the present invention is simple and easy, and is suitable for industrial production.
[0029] 4. The preparation of the present invention has better solubility, less change in the content of each impurity, and better stability. DETAILED DESCRIPTION
[0030] The present invention is further illustrated below through the description of specific implementation modes, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the scope of the present invention.
[0031] Test Example 1:
[0032] Prescription Screening Test 1
[0033] Take 8.1g of aspirin (content 99.9%, total impurities 0.09%), and prepare aluminum-magnesium aspirin tablets according to the following prescription (see Table 1). Test the hardness, dissolution and related substances. The results are shown in Table 2:
[0034] Table 1 Aluminum magnesium aspirin tablets prescription screening 1 (unit: g)
[0035]
[0036] Prescription 1 Preparation method
[0037] (1) Pass aspirin, aluminum glycolate, and heavy magnesium carbonate through an 80-mesh sieve respectively for later use;
[0038] (2) dissolving triethyl citrate and povidone K30 in water to prepare a 17.5% (w / w) povidone K30 solution as an adhesive solution;
[0039] (3) weighing a prescribed amount of aspirin, aluminum glycolate, heavy magnesium carbonate, methacrylate copolymer and corn starch and placing them in a fluidized bed granulator, spraying and granulating them with the binder solution prepared in step (2), drying and tableting to obtain aluminum-magnesium aspirin tablets;
[0040] (4) coating with a coating solution to obtain aluminum-magnesium aspirin coated tablets; the coating solution is a mixture of mannitol, titanium dioxide, and 5.64 g of water.
[0041] Prescription 2 Preparation method
[0042] (1) dissolving triethyl citrate and povidone K30 in water to prepare a 17.5% (w / w) povidone K30 solution as an adhesive solution;
[0043] (2) sieving the corn starch, mixing it with the binder solution, and granulating it in one step to obtain auxiliary material granules for later use;
[0044] (3) wet granulating aluminum glycolate, heavy magnesium carbonate, a binder solution, and an alkyl methacrylate copolymer to obtain aluminum-magnesium particles;
[0045] (4) The aluminum-magnesium particles obtained in step 2 are coated with a coating solution to obtain coated aluminum-magnesium particles; the coating solution is a mixture of mannitol, titanium dioxide, and 5.64 g of water.
[0046] (5) Aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and the filler are mixed and compressed to obtain tablets.
[0047] Prescription 3 Preparation method
[0048] (1) After sieving corn starch, mix it with a binder solution I (1.99 g mannitol, 8 g water), and perform one-step granulation to obtain auxiliary material granules for later use;
[0049] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II (triethyl citrate, povidone K30, 1 g of water), and methacrylate amine alkyl copolymer to obtain aluminum-magnesium particles;
[0050] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution comprises 1.41 g of mannitol, titanium dioxide, and 5.64 g of water.
[0051] (4) Aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch are mixed and tableted to obtain a final product.
[0052] Prescription 4 Preparation method
[0053] (1) After sieving corn starch, mix it with a binder solution I (1.19 g mannitol, 0.243 g pregelatinized starch, and 4.76 g water) and perform one-step granulation to obtain auxiliary material granules for later use;
[0054] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, binding liquid II (triethyl citrate, povidone K30, 1 g of water), and methacrylate aminoalkyl copolymer to obtain aluminum-magnesium particles;
[0055] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution comprises 1.41 g of mannitol, 0.357 g of pregelatinized starch, titanium dioxide, and 5.64 g of water;
[0056] (4) Aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch are mixed and tableted to obtain a final product.
[0057] Prescription 5 Preparation method
[0058] (1) After sieving microcrystalline cellulose and corn starch respectively, mix them with a binder solution I (1.19 g of mannitol, 0.243 g of pregelatinized starch, and 4.76 g of water) and perform one-step granulation to obtain auxiliary material granules for later use;
[0059] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II (triethyl citrate, povidone K30, 1 g of water), and methacrylate amine alkyl copolymer to obtain aluminum-magnesium particles;
[0060] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution is 1.41 g of mannitol, 0.357 g of pregelatinized starch, titanium dioxide, and 5.64 g of water;
[0061] (4) Aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch are mixed and tableted to obtain a final product.
[0062] Prescription 6 Preparation method
[0063] (1) After sieving microcrystalline cellulose and corn starch respectively, mix them with a binder solution I (1.19 g of mannitol, 0.243 g of pregelatinized starch, and 4.76 g of water) and perform one-step granulation to obtain auxiliary material granules for later use;
[0064] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II (triethyl citrate, povidone K30, 1 g of water), and methacrylate amine alkyl copolymer to obtain aluminum-magnesium particles;
[0065] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution is a mixture of 1.41 g of mannitol, 0.357 g of pregelatinized starch, titanium dioxide, and 5.64 g of water;
[0066] (4) mixing aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch, and tableting to obtain a semi-finished tablet;
[0067] (5) Drying the semi-finished tablet obtained in step 4 to obtain a final product.
[0068] The basic indicators of the prepared aluminum-magnesium particles, such as fluidity, hygroscopicity, hardness, disintegration time, and solubility, were evaluated to screen out a better prescription. The results are shown in Table 2.
[0069] Hygroscopicity test: High humidity test: The test samples (aluminum-magnesium particles obtained in Test Examples 2 to 6) were opened and placed in a constant humidity sealed container at 25°C and a relative humidity of 90%±5% for 10 days. Samples were taken on the 5th and 10th days, and the moisture absorption weight gain was calculated.
[0070] Table 2 Prescription evaluation results
[0071]
[0072]
[0073] The test shows that: 1. Aluminum-magnesium particles are granulated, coated and dried separately to remove the crystal water in aluminum glycolate and the adsorbed water of heavy magnesium carbonate. After tableting, built-in desiccant particles are formed, which can effectively reduce the hydrolysis of aspirin; 2. Adding microcrystalline cellulose to the granulation formula of aluminum-magnesium particles will also accelerate the drying speed and moisture absorption speed of aluminum-magnesium particles; 3. The weakly alkaline aluminum-magnesium particles are coated with neutral materials (mannitol + pregelatinized starch / or corn starch slurry) to isolate the opportunity of aluminum-magnesium contacting aspirin, which significantly reduces the catalytic effect of aluminum-magnesium ions and weak alkalinity on the hydrolysis of aspirin, and can effectively reduce the hydrolysis of aspirin. In particular, prescription 6 adds drying and dehydration of the final product on the basis of the preparation process of prescription 5, which significantly improves the product stability.
[0074] Preparation Example
[0075] Example 1
[0076] Prescription (weight unit: g)
[0077]
[0078] Preparation method
[0079] (1) After sieving microcrystalline cellulose and corn starch respectively, mix them with a binder solution I (1.19 g of mannitol, 0.243 g of pregelatinized starch, and 4.76 g of water) and perform one-step granulation to obtain auxiliary material granules for later use;
[0080] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II (triethyl citrate, povidone K30, 1 g of water), and methacrylate amine alkyl copolymer to obtain aluminum-magnesium particles;
[0081] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution is a mixture of 1.41 g of mannitol, 0.357 g of pregelatinized starch, titanium dioxide, and 5.64 g of water;
[0082] (4) mixing aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch, and tableting to obtain a semi-finished tablet;
[0083] (5) Drying the semi-finished tablet obtained in step 4 to obtain a final product.
[0084] Example 2
[0085] Prescription (weight unit: g)
[0086]
[0087] Preparation method
[0088] (1) After sieving microcrystalline cellulose and corn starch respectively, mix them with a binding solution I (11.9 g mannitol, 2.43 g pregelatinized starch, and 47.6 g water) and perform one-step granulation to obtain auxiliary material granules for later use;
[0089] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II (triethyl citrate, povidone K30, 10 g water), and methacrylate amine alkyl copolymer to obtain aluminum-magnesium particles;
[0090] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution is a mixture of 14.1 g of mannitol, 3.57 g of pregelatinized starch, titanium dioxide, and 56.4 g of water;
[0091] (4) mixing aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch, and tableting to obtain a semi-finished tablet;
[0092] (5) Drying the semi-finished tablet obtained in step 4 to obtain a final product.
[0093] Example 3
[0094] Prescription (weight unit: g)
[0095]
[0096] Preparation method
[0097] (1) After sieving microcrystalline cellulose and corn starch respectively, mix with a binder solution I (119 g mannitol, 24.3 g pregelatinized starch, 476 g water), and perform one-step granulation to obtain auxiliary material granules for later use;
[0098] (2) wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, binding liquid II (triethyl citrate, povidone K30, 100 g water), and methacrylate amine alkyl copolymer to obtain aluminum-magnesium particles;
[0099] (3) coating the aluminum-magnesium particles obtained in step 2 with a coating solution to obtain coated aluminum-magnesium particles; the coating solution is a mixture of 141 g of mannitol, 35.7 g of pregelatinized starch, titanium dioxide, and 564 g of water;
[0100] (4) mixing aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and corn starch, and tableting to obtain a semi-finished tablet;
[0101] (5) Drying the semi-finished tablet obtained in step 4 to obtain a final product.
[0102] Test methods
[0103] 1. Content determination (Chinese Pharmacopoeia 2020 Edition, Part IV, General Rules 0512).
[0104] Chromatographic conditions and system suitability test Octadecylsilane bonded silica gel was used as filler; 0.15% phosphoric acid and 0.025% acetic acid in water-0.15% phosphoric acid and 0.025% acetic acid in acetonitrile solution
[0105] (62:38, V / V) as the mobile phase; the detection wavelength is 276nm. The column temperature is 40℃. Weigh appropriate amounts of salicylic acid (impurity C) and aspirin reference substance, add 1% glacial acetic acid in methanol solution to dissolve and dilute to make a mixed solution containing about 0.8mg aspirin and 6μg salicylic acid per 1ml. Take 10μl and inject it into the liquid chromatograph, and record the chromatogram.
[0106] Determination method: Prepare freshly, take 5 tablets of this product and place them in a 250ml volumetric flask, accurately add 25ml of ethylparaben internal standard solution, add 150ml of 0.3% phosphoric acid in methanol solution, place in an oscillator and shake for 40 minutes, dilute to the mark with 0.3% phosphoric acid in methanol solution, and shake well. Take the above solution and put it into a stoppered centrifuge tube, centrifuge at 5000 rpm for 5 minutes, take the upper layer of liquid as the test solution, accurately measure 10μl and inject it into the liquid chromatograph, and record the chromatogram; accurately weigh 81mg of aspirin reference substance and place it in a 50ml volumetric flask, accurately transfer and add 5ml of ethylparaben internal standard solution, add 0.3% phosphoric acid in methanol solution and dissolve and dilute to the mark, shake well, and determine in the same way. Calculate by peak area according to the external standard method.
[0107] [Related substances] Take 5 tablets of this product and place them in a 250ml volumetric flask, add 175ml of 0.3% phosphoric acid in methanol solution, shake in an oscillator for 40 minutes, dilute to the mark with 0.3% phosphoric acid in methanol solution, and shake well. Put the above solution into a stoppered centrifuge tube and centrifuge at 5000 rpm for 5 minutes. Take the supernatant. (Inject within 30 minutes after preparation.) Accurately weigh 16.2mg of salicylic acid reference substance and place it in a 100ml volumetric flask, add 0.3% phosphoric acid in methanol solution to dissolve and dilute to the mark, shake well, as the salicylic acid (impurity C) reference substance stock solution, accurately measure 5ml of salicylic acid (impurity C) reference substance stock solution and place it in a 50ml volumetric flask, add 0.3% phosphoric acid in methanol solution to dissolve and dilute to the mark, shake well, seal and store at room temperature, as the reference solution. Accurately measure an appropriate amount of the control solution and quantitatively dilute it with 0.1mol / L hydrochloric acid solution to make a solution containing about 0.2μg per 1ml as the sensitivity solution. Determine according to high performance liquid chromatography (General Rules 0512 of the Fourth Part of the 2020 Edition of the Chinese Pharmacopoeia). Use octadecylsilane bonded silica gel as a filler; use an aqueous solution of phosphoric acid-acetic acid (6ml of 85% phosphoric acid and 1ml of 99.5% acetic acid diluted to 4000ml with water) as mobile phase A; use an acetonitrile solution of phosphoric acid-acetic acid (6ml of 85% phosphoric acid and 1ml of 99.5% acetic acid diluted to 4000ml with acetonitrile) as mobile phase B and perform linear gradient elution according to the table below. The column temperature is 40°C. Measure 10μl of the sensitivity solution and inject it into the liquid chromatograph, with 237nm as the detection wavelength, and the signal-to-noise ratio of the peak height of the main component chromatographic peak should be greater than 10. Then accurately measure 10 μl of the test solution, reference solution and each impurity mixed reference solution, respectively, and inject them into the liquid chromatograph, use 237 nm as the detection wavelength, and record the chromatogram.
[0108]
[0109] Table 3 List of related impurities
[0110]
[0111]
[0112] The dissolution was determined according to the dissolution and release method (Method 2, Part 4, General Rules 0931, Chinese Pharmacopoeia 2020 Edition).
[0113] The dissolution conditions were: 900 ml of hydrochloric acid solution (7.65→1000) as the dissolution medium, a rotation speed of 50 revolutions per minute, and operation according to the law. Samples were taken after 30 minutes.
[0114] Take 10 ml of the dissolution solution of the test sample, filter it, and take the filtrate.
[0115] Aspirin reference solution is freshly prepared before use. Take an appropriate amount of aspirin reference, weigh it accurately, add dissolution medium to dissolve it and quantitatively dilute it to make a solution containing about 90 μg per 1 ml.
[0116] Salicylic acid reference solution Take an appropriate amount of salicylic acid reference, weigh accurately, add dissolution medium to dissolve and quantitatively dilute to make a solution containing approximately 18 μg per 1 ml.
[0117] The determination method is according to the UV-visible spectrophotometry (General Rules 0401 of Part IV of the Chinese Pharmacopoeia 2020 Edition).
[0118] Take salicylic acid reference solution, set 276nm as the measurement wavelength (λ2), select the isosbestic point wavelength at 324nm±1nm as the reference wavelength (λ1). Require ΔA=|Aλ2-Aλ1|<0.005, then measure the absorbance of aspirin reference solution and test solution at λ2 and λ1 wavelengths respectively, calculate the absorbance difference (ΔA) of each, and calculate the solubility of aspirin;
[0119] Take aspirin reference solution, salicylic acid reference solution and test solution, and measure the absorbance at a wavelength of 303nm. The interference of dissolved aspirin on the absorbance of the test solution must be subtracted. Calculate the salicylic acid solubility based on the absorbance correction value of the test solution at 303nm (ΔA' = absorbance of the test solution - absorbance of the aspirin reference solution × aspirin solubility).
[0120] Multiply the measured salicylic acid solubility by 1.304 and add the aspirin solubility to obtain the release amount of this product.
[0121] The limit of 65% of the labeled amount shall comply with regulations.
[0122] The aluminum-magnesium aspirin tablets (II) (aluminum-plastic packaging) obtained from Examples 1 to 3 and the reference preparation (Japanese Lion aluminum-magnesium aspirin tablets (II) commercial product) were subjected to an accelerated 6-month stability test (40±2°C, RH75±5%). The aspirin content, impurity content and solubility were determined by high performance liquid chromatography.
[0123] Table 4 Accelerated test data of aluminum-magnesium aspirin tablets Packaging: PVDC / PVC / aluminum foil blister, test conditions: temperature 40±2℃, humidity 75%±5%
[0124]
[0125] Note: Impurity F was not detected.
[0126] Conclusion: From the above table, it can be seen that the product prepared by the method of the present invention has good stability under high temperature and high humidity. The dissolution rate of the aluminum-magnesium aspirin tablet (II) of the present invention is more stable than that of the reference preparation aluminum-magnesium aspirin tablet (II); and the degradation impurities are significantly less than those of the reference preparation.
Claims
1. A pharmaceutical composition of aluminum magnesium aspirin, characterized in that The pharmaceutical composition is composed of the following ingredients in parts by weight: 81 parts by weight of aspirin, 11 parts by weight of aluminum glycolate, 22 parts by weight of heavy magnesium carbonate, 5-10 parts by weight of weakly alkaline or neutral gastric-soluble polymer, 0.5-1 parts by weight of plasticizer, 4-25 parts by weight of microcrystalline cellulose, 10-40 parts by weight of neutral fast-dissolving material, 15-50 parts by weight of filler, 1-5 parts by weight of binder, titanium dioxide and water; The weakly alkaline or neutral gastric soluble polymer is an alkyl methacrylate copolymer; The plasticizer is triethyl citrate; The neutral instant material is mannitol and pregelatinized starch; The above-mentioned pharmaceutical composition is prepared into aluminum magnesium aspirin tablets, and the preparation method of the tablets is as follows: Step 1: After sieving microcrystalline cellulose and filler respectively, mix them with binding solution I, perform one-step granulation, and obtain auxiliary material particles for standby use; wherein the binding solution I comprises mannitol, pregelatinized starch and water, wherein the weight ratio of mannitol, pregelatinized starch and water is: 0.2-0.3: 0.04-0.06: 0.8-1.2; Step 2: wet granulating aluminum glycolate, heavy magnesium carbonate, microcrystalline cellulose, a binding solution II, and a weakly alkaline or neutral gastric-soluble polymer to obtain aluminum-magnesium particles; wherein the binding solution II comprises povidone K30, triethyl citrate, and water, wherein the weight ratio of povidone K30, triethyl citrate, and water is 0.10-0.25:0.08-0.12:0.8-1.2; Step 3: coating the aluminum-magnesium particles obtained in step 2 with a coating liquid to obtain coated aluminum-magnesium particles; Step 4: mixing aspirin, the auxiliary material particles obtained in step 1, the coated aluminum-magnesium particles obtained in step 3, and the filler, and tableting to obtain a semi-finished tablet; Step 5: drying the semi-finished tablet obtained in step 4 to obtain a final product; the drying is performed by vacuum drying or forced air drying; The coating liquid comprises mannitol, pregelatinized starch, titanium dioxide and water, wherein the weight ratio of mannitol, pregelatinized starch, titanium dioxide and water is 0.2-0.3: 0.06-0.07: 0.03-0.04: 0.8-1.2.
Citation Information
Patent Citations
New preparation method for aspirin-containing compound preparation
CN102198147A